Corporate environmental performance, environmental management and firm risk. (17th December 2019) - Xue, Bai; Zhang, Zhuang; Li, Pingli
Abstract: Using a sample of 1, 632 U.K. firm‐year observations from 2002 to 2013, this paper investigates the impact of multidimensional corporate environmental performance (CEP) on firm risk. Considering two dimensions of CEP, namely environmental management performance (EMP) and environmental operational performance (EOP), we find that EMP serves as an effective mechanism in reducing firm risk, and such an effect is mainly driven by the manufacturing sector. Meanwhile, there is no clear association between EOP and firm risk. However, our findings highlight a moderating effect of EOP on the relationship between negative EMP and firm risk. This provides new insights into the value of multidimensional CEP and suggests that the complex relationship between outcome‐ and process‐based environmental performance is important for understanding the real effects of CEP on firm risk. Our results have important implications for managerial decision‐making in strategy and risk management, as well as for policymaking in environmental regulation.